Energy-Dispersive X-ray Microanalysis of a Herbal Antimicrobial: Fifatrol (Asian Journal of Pharmaceutics (AJP), 2023)
Ayurveda is a natural system of medicine, which is acceptable worldwide now days. Most of the medications used in thistraditional system belong to natural drugs derived from the plants and other natural resources. These naturally derivedantimicrobial drugs are equally effective as the other synthetically designed drugs of other medicinal systems against thedifferent microbes. A detailed compositional analysis of any drug is very necessary to establish its role. Energy-dispersiveX-ray (EDX) or energy-dispersive spectroscopy is a kind of microanalysis of any elemental structure. It is based on thedetection of characteristic X-rays generated under electron microscopy. It provides both quantitative as well as qualitativeinformation in elemental analysis. It is very important and useful technique to study a new drug to understand the drugdelivery as well as nanoparticles in composition of any drug. In the present study, we have used a plant based extractantimicrobial drug named Fifatrol for detailed compositional analysis by EDX microanalysis under scanning electronmicroscope to see the different proinflammatory and anti-inflammatory elements such as Ca, S, O, Na, and B.